Backward stimulated raman scattering - Morrison, G R (Department of Physics, 2024)
We present both a theoretical overview and an experimental investigation of the stimulated Raman effect. A new prediction is made for the steady state linewidth of the forward Stokes output in the presence of a depleted pump. The theory is developed with the aim of gaining an understanding of the mechanism which favours stimulated Raman output in the backward direction. The experimental investigation with hydrogen as the Raman medium, was confined to a transient regime. We were therefore unable to verify our prediction for the steady state Stokes linewidth. A rare observation of anti-Stokes radiation in the backward direction was made. The general observations shed light on the question of the mechanism responsible for 'predominantly' backward Stokes output.